A express?o do futuro verbal na escrita escolar de Irar?-BA - Figuereido, Joana Gomes dos Santos (2015)
The verbal future tense in Portuguese is a variable phenomenon currently expressed by the verb forms: the simple future tense, the periphrasis with go + infinitive, the indicative present tense, and the gerundive future form. Among them, the simple future tense is the standard way, and the periphrastic future form is considered by grammarians like a colloquial form of the language. Several studies (GIBBON, 2000; OLIVEIRA, 2006; BRAGAN?A, 2008; SILVA, 2010; TESCH 2011; SANTOS, 2012) have attested to this variable phenomenon throughout history of the Portuguese language and point to the implementation of the periphrastic way of to go + infinitive as a possible replacement of the simple future tense. According to these studies, this change is almost complete in speech and is already invading writing. With this information about the uses of the verbal future tense in Portuguese, in this study, we analyzed data of high school students from public and private schools in the city of Irar?-Ba, within a variational and functionalist perspective, with a synchronic study, in order to observe the presence of the periphrastic future form in school texts, considering the process of grammaticalization. The results of the verbal future tense in school writing of the first, second and third classes of high school, with the control of various groups of linguistic and sociolinguistic, factors, showed that the variant that more customarily occurs in spoken language (the periphrastic future form) is also present in written language. The results show that the phenomenon under study is motivated by factors such as type of school, verbal paradigm, residential area, syntactic status of verb, verb conjugation, thematic role of the subject, semantic nature of the verb, type of subject and type of verb. It was evident through the review that there is an ongoing change process towards the simple future form, more used in texts written by speakers said "cults", be replaced by the periphrastic future form, commonly founded in speech, suffering less normative pressures.